Wear in hard metal check valves: In-situ surface modification through tribolayer formation in dry contact. (October 2021) - Blutmager, A.; Varga, M.; Cihak-Bayr, U.; Friesenbichler, W.; Mayrhofer, P.H.
Abstract: Tools in injection moulding units, especially the check valves, can suffer dry hard metal - hard metal contact under severe conditions, thus experiencing increased wear. For the present study, various hard metal pairings were investigated using dry pin-on-disc tests to simulate the tribosystem of the check valve. Hard metal discs with Wx C particle sizes between 0.9 and 3 μm and binder contents between 9 and 17.5 wt. %, were tested against similar pins with smaller Wx C particles. Results show that the cracking of carbides is the major wear mechanisms and that decreased Wx C particles sizes together with decreased binder contents lead to lower wear rates. The combination of the hard metal with the smallest Wx C particles and the lowest hardness differences between pin and disc leads in this case to a beneficial material transfer and tribolayer formation, resulting in increased wear resistance of both sliding counterparts, promising a lifetime enhancement of the check valves. Highlights: Dry hard metal – hard metal contact was simulated in a pin-on-disc setup. Tribolayer formation offered an effective in-situ evolution of wear protection. The tribolayer consists of binder, small Wx C grains/fragments and oxides. Similar Wx C particle sizes in the counterbodies support optimal tribolayer coverage. Smallest Wx C particle sizes entailed lowest wear rates.